2018
DOI: 10.3892/mmr.2018.9316
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‑targeted microbubble destruction‑mediated miR‑205 enhances cisplatin cytotoxicity in prostate cancer cells

Abstract: MicroRNAs (miRNAs) are non-coding ~20 nucleotides long sequences that function in the initiation and development of a number of cancers. Ultrasound-targeted microbubble destruction (UTMD) is an effective method for microRNA delivery. The aim of the present study was to investigate the potential roles of UTMD-mediated miRNA (miR)-205 delivery in the development of prostate cancer (PCa). In the present study, miR-205 expression was examined by reverse transcription-quantitative polymerase chain reaction assay. m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Ji et al (38) investigated the application of UTMD in miR-133a delivery and found that UTMD-mediated miR-133a inhibited tumor growth and improved the survival rate in a breast cancer mouse model, suggesting the therapeutic potential of UTMD-mediated miR-133a for breast cancer treatment. UTMD successfully enhanced the transfer of miR-205, as evidenced by the significant increase in miR-205 expression in prostate cancer cells, leading to suppressed tumor cell proliferation, migration and invasion and enhanced cell apoptosis (39). However, to the best of our knowledge, the application of UTMD in the treatment of NSCLC has rarely been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Ji et al (38) investigated the application of UTMD in miR-133a delivery and found that UTMD-mediated miR-133a inhibited tumor growth and improved the survival rate in a breast cancer mouse model, suggesting the therapeutic potential of UTMD-mediated miR-133a for breast cancer treatment. UTMD successfully enhanced the transfer of miR-205, as evidenced by the significant increase in miR-205 expression in prostate cancer cells, leading to suppressed tumor cell proliferation, migration and invasion and enhanced cell apoptosis (39). However, to the best of our knowledge, the application of UTMD in the treatment of NSCLC has rarely been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ectopic expression of miR-205 increased the apoptotic dead cells (PI and Annexin V positive) after cisplatin treatment from 5.42% (Cisplatin alone) to 26.88% (Cisplatin + UTMD mediated miR-205). Additionally, cisplatin’s ability to inhibit the cellular migration was further enhanced with miR-205 [ 201 ]. In cisplatin resistant glioma cells, overexpression of miR-205 reversed the drug resistance via targeting E2F1.…”
Section: Therapeutic Applications Of Mir-205mentioning
confidence: 99%
“…sncRNAs are also involved in the development of platinum-based drug resistance in prostate cancer [ 33 ]. In prostate cancer cells, miR-205 enhances cisplatin toxicity through the induction of cleaved caspase-9 and cytochrome c [ 9 ]. In addition, a miR-425-5p mimic suppresses the expression of cyclin D1 and targets GSK3β, to increase the sensitivity of prostate cancer cells to cisplatin [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies over the past 20 years have demonstrated the possibility of using sncRNAs as biomarkers for the early diagnosis of cancer [ 8 ]. Moreover, sncRNAs regulate the sensitivity of cancer cells to anticancer agents [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%